The Effectiveness of Amalish in Transforming English Language Learning in Primary Schools - Ratih Laily Nurjanah; Ulya Himawati; Ersila Devy Rinjani (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2026)
The integration of digital technology in primary education requires innovative platforms that support not only instructional delivery but also broader educational transformation. This study aims to evaluate the effectiveness of Amalish (Animated English) in transforming English language learning in primary schools. Unlike previous studies that primarily focus on learning outcomes or media effectiveness, this study examines Amalish as an integrated digital platform that simultaneously supports learning management, teacher digital competence, instructional media production, and technology utilization. A descriptive quantitative design was employed involving 15 teachers from SDN 03 Klepu Semarang, Indonesia. Data were collected through questionnaires, observations, and documentation and analyzed using descriptive statistics by calculating mean scores and standard deviations across the measured dimensions. The findings indicate that all dimensions achieved a “Very High” category, including learning management (M = 4.33), teacher digital competence (M = 4.83), instructional media production (M = 4.50), and technology utilization (M = 5.00). The results suggest that Amalish effectively supports teachers in integrating digital technology into instructional practices while simultaneously improving learning management and instructional monitoring processes. This study contributes to the literature on digital language learning by demonstrating that educational technology can function not only as an instructional tool but also as a catalyst for pedagogical, technological, and managerial transformation in primary education. The findings provide practical implications for schools seeking to implement sustainable digital transformation through integrated learning platforms.